Metacognitive profiles in schizophrenia and bipolar disorder: Comparisons with healthy controls and correlations with negative symptoms. (November 2017) - Popolo, Raffaele; Smith, Elizabeth; Lysaker, Paul H.; Lestingi, Krizia; Cavallo, Francesca; Melchiorre, Luisa; Santone, Cristina; Dimaggio, Giancarlo
Abstract: While deficits in metacognition, or the ability to notice and reflect upon mental states has been observed in schizophrenia and linked with poorer concurrent and future function, it is unknown whether these deficits are unique to schizophrenia. Accordingly, this study assessed metacognition using the Metacognitive Assessment Scale–Abbreviated (MAS-A) and the Metacognitions Questionnaire– 30 (MCQ-30) among 26 adults with schizophrenia, 23 with bipolar disorder and 23 healthy controls. Symptom levels of the psychiatric groups were assessed with the Brief Psychiatric Rating Scale. ANCOVA controlling for age and education revealed that the schizophrenia group had lower scores on the MAS-A total and its subscales compared to the bipolar group and healthy controls. The bipolar disorder group also had lower MAS-A scores than the healthy control group. No group differences were found for the MCQ-30. Examination of symptom correlates revealed MAS-A scores were most commonly related to negative symptoms in both clinical groups. The total score and need for control subscale of MCQ-30 was related to total symptomatology and positive symptoms in patients with bipolar disorder. Correlations between the two measures of metacognition revealed that higher MAS-A scores were significantly related to lower scores on the Need to Control Thoughts MCQ-30 subscale. Highlights: Serious mental illness is linked with metacognitive deficits in metacognition. Metacognitive beliefs and capacities in schizophrenia, bipolar disorder and in healthy controls were compared. The schizophrenia group had poorer level of synthetic metacognition than the bipolar group which had poorer synthetic metacognition than healthy controls. No differences were found in levels of maladaptive metacognitive beliefs between groups.